СОнГУУЛЬ Ба кОндОРСеГИйн ПаРадОкС, ЭРРОУГИйн ТеОРеМ - Ц.ГАНБОЛД (Politology, 2023)
Done well, electoral system design can add to the momentum of political change, encourage popular participation, and enable the emergence of legitimate representatives who are capable of handling a wide range of needs and expectations, immediarely and in the future. Done badly, it can derail progress towards democracy or even political stability. To be successful, electoral system design processes must build build understanding and trust-not just among politicians and election administrators, but among civil society organizations, among commentators, and above all among the citizens of a country undergoing democratic reform. Electoral systems must be designed not only to work under current situations but also to accommodate future changes in attitudes and behavior as electoral incentives change. They can contribute to the development of stable democracy or they can be a major stumbling block to it.